PIC Microcontroller Programming: in 10 captivating lessons (JAL) - Bert, Van Dam (Elektor, 2013)
Using the lessons in this book you learn how to program a microcontroller. You'll be using JAL, a free but extremely powerful programming language for PIC microcontrollers, which enjoys great popularity in the hobby world. Starting out from scratch virtually, you slowly build up the knowledge. No previous knowledge is needed: anyone can get started with this book. Assuming you have absorbed all lessons - meaning you have actually completed all the exercises - you should be confident to write PIC microcontroller programs, as well as read and understand programs written by other people.